A Valuation Methodology and Pricing Analysis of Clickoptions. - Quesney, Alexis (2007)
In the past twenty years, derivative finance has amazingly increased to become a core business in many banks and financial institutions. Until recent years, this development had only benefited to investors that had significant wealth, that is to say financial institutions and multinational corporations. Notwithstanding, things have changed and financial derivatives are now available to a great majority of investors, including private investors. This great progress has been achieved mostly thanks to binary betting (financial, sport, and political binary betting). This branch of finance has been first introduced in Anglo-Saxon countries. The initiative in France is awarded to Socirale, a global retail and investment bankwhich created a subsidiary specialized in financial derivatives, ClickOptions. It is tradingbinary and digital options targeting a clientele mostly composed of private investors. The products are very user-friendly and simple to understand as they do not require any financial background prior to trading them. As a consequence they attracted a lot of people. The aim of this dissertation is to uncover the valuation mechanisms of such financial derivatives. In the first chapters, I explain define clickoptions. Then, I provide a significant theoretical literature review on derivative valuation. Using this set of knowledge, I create three valuation models for clickoptions using Visual Basic for Application, test them and compare and analyze the outputs of those models with real market prices. The three models created are based on analytical formulas, the binomial tree method and the Monte-Carlo simulation method. The main challenges of this dissertation were to deal with financial products at first sight very simple but very complex in their valuation mechanism, as well as writing on a topic that had never been studied before in past literature. This dissertation leaves an open door on more research about clickoptions valuations mechanisms as well as trading and hedging strategies with clickoptions.